ANALYSIS OF DOMAIN MONITORING AND EVALUATION COBIT MATURITY LEVEL IN GAME DEVELOPMENT COMPANY - Putri Nastiti; Kathryn Widhiyanti (Jurnal Riset Informatika, 2021)
Abstract There are many opinions that information technology governance is only suitable to be applied by large-scale companies. However, this has not been proven to be true. Many small and medium-sized startups fail because they do not have good governance plans. This means that even small and medium-sized companies also need proper IT implementation planning. The purpose of this study was to measure the maturity level of information technology governance, particularly in terms of monitoring and evaluating IT performance, implementing internal controls, and compliance with company external regulations. Based on calculations, this game development company is at maturity level 3 (Defined Process). In addition, it was found that the biggest gap was in the Skill and Expertise attributes and the Goals and Measurement attributes. This study also provides recommendations for companies based on gap analysis in each process.